Bacteroides Spp. Blebitis, Keratitis, and Endophthalmitis Following Uncomplicated Trabeculectomy. Issue 7 (July 2019) - Parker, Jack S.; Dockery, Philip W.; Parker, John S.; Crosson, Jason N.; Kilpatrick, David; Samuels, Brian
Abstract : Purpose: To describe the first known case of Bacteroides spp. related blebitis, keratitis, and endophthalmitis following uncomplicated trabeculectomy. Methods: This was a case report and literature review. Case: A 63-year-old immunocompetent white male underwent uncomplicated trabeculectomy of his right eye. Two weeks later, a blebitis with adjacent keratitis was diagnosed, progressing over several days to endophthalmitis despite hourly topical fortified antibiotic therapy. Although gram stain and culture of the bleb surface, a conjunctival suture, the aqueous humor, and the vitreous were negative, topical real-time quantitative polymerase chain reaction testing disclosed the presence of Bacteroides spp. Following treatment with topical and intravitreal clindamycin and intravenous meropenem, all clinical evidence of infection resolved. Best spectacle–corrected visual acuity improved to 20/25 (0.8) subsequent to combined cataract extraction, intraocular lens implantation, and pars plana vitrectomy for persistent vitreous debris. Conclusions: Bacteroides may be a rare cause of postoperative blebitis, keratitis, and endophthalmitis. A favorable outcome may be attained, provided that an accurate diagnosis and effective treatment can be provided, which may be facilitated by real-time quantitative polymerase chain reaction in select cases.